Revisión de procesos biológicos para el aprovechamiento de pulpa de café residual (2021)
Due to the growing demand and consumption of the population in Colombia, Currently, in the processing of agricultural products, around 71,943,814 tons of residual biomass are generated per year between the production of coffee, corn, rice, and bananas, among others. The inadequate final disposal means that this waste ends up in sanitary landfills or incinerated, causing a direct negative environmental impact on nature, causing levels of contamination that affect all living beings, which is slowly causing the destruction of the common house where we live. Therefore, it should be taken into account that, in Colombia, coffee production is the most relevant agricultural sector in the country, in which approximately 942,327 tons are produced per year for commercialization, but it is causing worrying levels of contamination, since that the harvested bean process is done through wet milling to give it mild aromas and flavors, but the coffee pulp as a by-product is the biggest contaminant.